Sustainable Heating for Building Premises Using Solar Energy - R. Kharchi; S. Sami; S. Hakem; K. Imessad; S. Bouchaib; S. Larbi-youcef (New Horizons of Science, Technology and Culture Vol. 1, 2025)
The objective of this work is to demonstrate the importance of solar thermal systems for energy savings in buildings. The solar thermal system covers the heating needs of the offices. The solar thermal collectors are installed on the building’s terrace and are used to heat water. This water will be stored in the solar tank, then distributed to the premises by heat emitters. The building is located on the heights of Algiers. Based on the surface area of the premises to be heated, we sized the heating system and calculated the energy demand, which depends on the surface area of the collectors to be installed and the storage tank. TRNSYS software is used for dynamic simulation of the building’s performance. The annual energy requirements for heating amount to 2,754 kWh. This led to the installation of a 10 m² solar thermal collector field and a 500-litre solar tank. The useful energy of the solar collector field reached 500 kJ/h in June. This fully covers the heating demand (100%). For the summer season, this energy will be used to produce domestic hot water.